O tratamento de questões sociocientíficas na formação de futuros professores de ciências: possibilidades e desafios nas vozes dos licenciandos - Carnio, Michel Pisa UNESP]; Carvalho, Washington Luiz Pacheco de [UNESP] (My University, 2014)
The perspective STSE (Science-Technology-Society-Environment) was recently implemented in the training courses for science teachers in Brazil, and proposes greater coordination of scientific knowledge with subjective questions that constitute the science, enables discussion of the nature of science and its implications for social and environmental issues. The present work aims to contribute to training of science teachers that approximates the current demands of contemporary society. Having as theoretical reasons the implications of STSE Movement in science teaching, we bring some considerations on pedagogical practices of undergraduates in Biological Sciences held within its Supervised. Through content analysis of the speeches of undergraduates, we can identify contributions and limitations that treatment of socio-scientific issues (SSI) revealed in the process, putting to discuss some aspects that are tangent training teachers committed to a contextualized view of science and scientific training. It discusses, among them, the relationship theory and practice in supervised training of future teachers’ conceptions about the implications of the STSE perspective in science teaching and science teacher positioning ahead controversial themes.

A perspectiva CTSA (Ciência-Tecnologia-Sociedade-Ambiente) é recente nas grades horá- rias de cursos de formação de professores de ciências no Brasil e propõe maior articulação do conhecimento científico com questões subjetivas que constituem a ciência, possibilitando a discussão da natureza da ciência e suas implicações em questões sociais e ambientais. O presente trabalho almeja contribuir com uma formação de professores de ciências que se aproxime das atuais demandas da sociedade contemporânea. Tendo como fundamentação teórica as implica- ções do Movimento CTSA no ensino de ciências, trazemos algumas considerações sobre práticas pedagógicas de licenciandos em Ciências Biológicas realizadas no âmbito de seu Estágio Curricular Supervisionado. Por meio de análise de conteúdo das falas dos licenciandos, conseguimos identificar contribuições e limitações que o tratamento de questões sociocientíficas (QSC) evidenciou no decorrer do processo, colocando para discussão alguns aspectos que tangenciam uma formação de professores comprometida com uma visão contextualizada de ciência e de formação científica. Discute-se, entre eles, a relação teoria e prática no estágio supervisionado, as concepções dos futuros professores sobre as implicações da perspectiva CTSA no ensino de ciências e posicionamento do professor de ciências frente temáticas controversas.
The treatment of socio-scientific issues in science teacher training: opportunities and challenges in the voices of undergraduates
Keywords: Training teachers; STSE perspective; Supervised training; Teacher as intellectual; Formação de professores; Relações CTSA; Estágio supervisionado; Professor como intelectual